Operational and Financial Aspects for Delivering a Consortium Shared LMS - The MITOS Project. Issue 5 (4th July 2018) - Kouis, Dimitrios; Veranis, George; Papadatou, Eleni; Mitrou, Nikolaos
ABSTRACT: The Shared Library Management System (LMS) model is not a new concept. Lately, many libraries consortia have migrated to a shared LMS to reduce their services' total costs. The Hellenic Academic Libraries consortium has implemented a shared LMS service, hosted in a private owned cloud infrastructure for its members during the past years (known as the MITOS project). Recognizing the complexity and significance that joining a shared LMS represents, it is important for librarians and other decision makers to have access to the MITOS experience for operational, technical and financial aspects, during and after the transition.